MODERN VIEW ON THE FACTORS DETERMINING THE IMPROVEMENT OF KNITTED FABRICS - HIBELINDA, OLENA; SARIBYEKOVA, YULIYA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Knitted clothing is not without reason called the clothing of the 20th and subsequent centuries. Beautiful appearance, high hygiene and ease of use, the necessary durability and reliability favorably distinguish knitted outerwear and especially underwear from similar products made of fabrics. The knitwear industry in the 20th and 21st centuries developed at a higher pace than the production of fabrics and products made from them. It has wider technological capabilities and assortment opportunities for constant expansion and updating of the assortment in accordance with changes in fashion and market conditions. The knitwear subsector occupies a prominent place in the light industry of Ukraine. Today, both well-known Ukrainian enterprises and many new enterprises of various forms of ownership are engaged in the production of knitted clothing. Ukrainian knitwear manufacturers use a variety of domestic technologies, as well as technological processes developed abroad. The growth of the share of knitwear in the total world production of fibrous materials is ensured by the high consumer properties of knitted fabrics. The knitwear industry produces a wide range of products, many of which are indispensable or more desirable than products made from fabric. Systematic studies have shown that the quality of knitted garments is influenced by many factors. The implementation of plans to increase the volume of garment production, increase labor productivity, improve quality and expand the range of products largely depends on the technological characteristics of the knitted fabric used. The problem of competitiveness of knitted garments produced by domestic enterprises is a complex set of interrelated organizational, information and technological, technical and economic tasks. Solving these tasks is a fundamental prerequisite for reducing the cost of production, improving its quality and increasing the competitive presence of production in the consumer goods market. Taking into account the further growth of requirements for the quality of sewing products, the issues of improving a number of operations and processes, introducing new technologies and providing them with technical means are gaining particular importance. Effective solutions to these problems must be accompanied by a determined choice and forecasting of the assortment, technological modes and parameters, and the basics of design and calculation of processes.